ENVIRONMENTAL EDUCATION THROUGH ELO RIVER RAFTING ECOTOURISM MAGELANG REGENCY - Ahmad Muhlisin; Moch Malik Al Firdaus; Siswanto Siswanto (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2020)
This community service aims to improve tour guides’ skills in delivering environmental education in English and enhance their environmental awareness attitude. The activity implementation method is direct method from preparation, implementation, evaluation, and discussion of follow-up efforts. The activity results indicate that the activity run well in accordance with the pre-determined targets and outcomes. The activity conducted provides an illustration that the training generates added value in environmental education conveyed in English to the visitors as well as to the tour guides in their attitude toward the environment. Follow-up efforts to be executed next year include creating a profile of each tree around the Elo River and environmental-themed photo spots.